An analysis of perceived usefulness of google scholar by the postgraduate students of the University of Ilorin, Nigeria (2017)
Background: Google Scholar provides user-friendly information resources and is very effective in finding information to satisfy various information needs, especially by the research students. However, despite its usefulness in satisfying information and research needs of the research students and researchers as a whole, the lingering effect associated with it is drawing students away from libraries. Similarly, there have been limited studies conducted to examine the level of perceived usefulness of Google Scholar by the graduate students, particularly in the context of the University of Ilorin, Nigeria. Objectives: The study examined the perceived usefulness of Google Scholar by the postgraduate students of the University of Ilorin, Nigeria. Methods: A total of 223 postgraduate students selected through simple random sampling from 15 faculties that made up the University formed the sample for the study. A survey approach was adopted using a questionnaire to gather data from respondents. Six research questions were developed to guide the study. Results: The results demonstrate that the majority of respondents strongly agreed and agreed that they were aware of Google Scholar and usually used it. However, the respondents were not satisfied with Google Scholar as it does not either speed up their research or make their research easier. Google Scholar was considered useful because it covers broad topics in the area of interest and usually provides relevant articles related to the respondents’ search done through this platform. Conclusion: The study concluded by recommending, among others, that there is a need for orientation programmes to enhance the use of Google Scholar via the university library